Effect of surface nanocrystallization layer on formation process of low temperature ion sulphurizing layer. Issue 182 (24th July 2017) - Ba, Dema; Sun, Xiaofeng; Li, Xin; Qiu, Ji; Shi, Yupeng; Wang, Zheng
ABSTRACT: The sulfide layer was prepared on surface nanocrystallizated surfacing layer with the low temperature ion sulphurizing technology and, the microstructure of sulphurizing layers with different sulphurizing time was analyzed by SEM, EDS, TEM, and XRD analysis techniques. The analysis indicated that the effect of nanocrystallization on microstructure of sulphide layer was obvious at the beginning of sulfurizing, Compared with the non-nanocrystallization samples, the sulfide on nanocrystallization sample surface was fine and homogeneous particles; the sulfide layer was denser and the sulfide content dominated by FeS was higher. As sulphurizing time increasing, the sulfide layer on the surface of nanocrystallization sample, mainly composed of FeS and FeS 2 phase, was quite dense. The proportion of FeS2 phase of the surface nanocrystallization sample was lower than that of the non-nanocrystallization sample. The result indicated that the surface nanocrystallized surfacing layer after being could improve sulphurizing effect mainly due to the high activity and adsorptive property of the surface nanocrystallization layer.